Infertile Women’s Opinion Concerning Gestational Surrogacy: A Systematic Review and Meta-Analysis - MUSAVI, Sanaz (Iran J Public Health, 2020)
BACKGROUND: This systematic review and meta-analysis of the observational studies aimed at evaluating the infertile women’s attitude toward gestational surrogacy. METHODS: Published studies until Jan 2019 were searched using PubMed/MEDLINE, Scopus, EMBASE, Cochrane Library, ISI Web of Science, Proquest and Google scholar, MagIran, SID and IranMedex. Studies in English or Persian language surveyed attitudes toward surrogacy for infertile women published until Jan 2019. Animal studies and studies with poor methodological quality were excluded from the review. RESULTS: Six eligible studies including 1359 infertile women were identified. Of these, 559 and 742 women agreed and disagreed with surrogacy respectively. The overall event rate of positive attitude for surrogacy in infertile women was %39.7 (%95 CI=24.5 to 57.1, P=0.245). CONCLUSION: The infertile women’s attitude toward surrogacy is not strongly positive. We believe, more studies should be conducted among different socioeconomic, religious and cultural groups.